Pengukuran Efektivitas Marketing Communication PT Xl Axiata - Lazuardy, Ilham; Astri Wulandari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
PT XL Axiata, as a telecommunications company, has a mission to provide the best for customers in terms of products, services, technology, and value for money. One of the company's strategies in improving marketing communications and fulfilling XL customers' data needs is through the launch of Akrab data package. In this context, the activities carried out by PT XL Axiata's Integrated Marketing Communications, particularly the sale of the Akrab data package, have an important role in meeting the needs of people who are looking for affordable and competitive communication packages. The positive response from the public towards this program can largely be attributed to the efforts of Integrated Marketing Communications in selling the Akrab data package. This research uses Descriptive Qualitative method with case study analysis to describe and summarize various conditions, situations, and social phenomena that occur at PT XL Axiata as the object of research. Data were collected through interviews, and data processing using a triangulation approach, with inductive data analysis. The results of this study are communication carried out by XL resulting in Positive Brand Awareness, Structured and Responsive Communication, Increased Sales and Customer Satisfaction.